The Morphometric Analysis of Wadi Al - Qarn Basin By Using Geographical Information System (GIS) - طربوش أمين; ناصيف مريم (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Morphometric study is one of the most important recent ways in the study of water basins, according to the relationship between the physical characteristics of the studied basin area and the morphometric characteristics of its water drainage network. So, the natural characteristics of the Wadi Al - Qarn Basin area were studied, represented by topographic, geological, climate, surface water resources and measurement of the flow of the Wadi Qarn at the site of Al-Tkeieh, where its mouth to the Barada River, and the biological characteristics of the basin. Also, a database was built within the ArcCatalog program containing morphometric variables that resulted from the analysis of the digital elevation model DEM for the basin area – resolution (30) meters on the ArcMap program to extract and determine the water network and streams orders The study showed the local importance of Wadi Al-Qarn through the construction of the dam known by its name on it, and what is formed from the dam by a water surface known as Zarzar Lake, which has an important tourist destination in the Zabadani area - Damascus countryside. The research also concluded a completely physical study of the basin area, linking it with the formal, geometry, and terrain characteristics of the basin, as well as linking it with the morphometric characteristics of the basin water network.